Affinities on art and fascination - Dillon, Brian 1969- (The New York Review of Books, 2023)
"Brian Dillon was born in Dublin in 1969. His books include Essayism, The Great Explosion (shortlisted for the Ondaatje Prize), Objects in This Mirror, I Am Sitting in a Room, Sanctuary, Tormented Hope: Nine Hypochondriac Lives (shortlisted for the Wellcome Book Prize), and In the Dark Room, which won the Irish Book Award for nonfiction. His writing has appeared in The Guardian, The New York Times, London Review of Books, The Times Literary Supplement, Bookforum, frieze, and Artforum. He is the UK editor of Cabinet magazine and teaches creative writing at Queen Mary University of London"--
Keywords: Artists / Psychology; Communication in art